Characterization of a new platelet aggregating factor from crotoxin Crotalus durissus cascavella venom - Fonseca, F. V.; Antunes, E.; Morganti, R. P.; Monteiro, Helena S. A.; Martins, A. M. C.; Toyama, D. O.; Marangoni, S.; Toyama, M. H. (Springer, 2006)
In this article we investigated the platelet aggregating activity of whole crotoxin and its subunits isolated from Crotalus durissus cascavella venom. During the purification protocols of the venom, using HPLC molecular exclusion, we detected the presence of two different serine protease activities in the gyroxin fraction, and another in the crotoxin fraction, which induced strong and irreversible platelet aggregation, in addition to blood coagulation. From crotoxin, we isolated PLA(2), crotapotin (both fractions corresponding approximately 85% of whole crotoxin) and another minor fraction (F20) that exhibited serine protease activity. After a new fractionation on reverse phase HPLC chromatography, we obtained three other fractions named as F201, F202 and F203. F202 was obtained with high degree of molecular homogeneity with molecular mass of approximately 28 kDa and a high content of acidic amino residues, such as aspartic acid and glutamic acid. Other important amino acids were histidine, cysteine and lysine. This protein exhibited a high specificity for BApNA, a Michaelis-Menten behavior with Vmax estimated in 5.64 mu M/min and a Km value of 0.58 mM for this substrate. In this work, we investigated the ability of F202 to degrade fibrinogen and observed alpha and beta chain cleavage. Enzymatic as well as the platelet aggregation activities were strongly inhibited when incubated with TLCK and PMSF, specific inhibitors of serine protease. Also, F202 induced platelet aggregation in washed and platelet-rich plasma, and in both cases, TLCK inhibited its activity. The N-terminal amino acid sequence of F202 presented a high amino acid sequence homology with other thrombin-like proteins, but it was significantly different from gyroxin. These results showed that crotoxin is a highly heterogeneous protein composed of PLA(2), thrombin-like and other fractions that might explain the diversity of physiological and pharmacological activities of this protein.
Keywords: Crotalus durissus cascavella; snake venom; thrombin like; platelet aggregation